2022
DOI: 10.1101/2022.02.02.478736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced excitability of the hippocampal CA2 region and its contribution to seizure generation in a mouse model of temporal lobe epilepsy

Abstract: The hippocampal CA2 region, an area important for social memory, has been suspected to play a role in temporal lobe epilepsy (TLE) because of its resistance to the degeneration observed in neighboring CA1 and CA3 regions in both human and rodent models of TLE. However, little is known about whether alterations in CA2 properties serve to promote seizure generation or propagation. Here we have used the pilocarpine-induced status epilepticus (PILO-SE) model of TLE to explore the role of CA2. Ex vivo electrophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 64 publications
2
13
1
Order By: Relevance
“…We recently found that in the pilocarpine-induced status epilepticus mouse model of TLE there was an increase in CA2 intrinsic excitability associated with a loss of CA2 synaptic inhibition. Furthermore, chemogenetic silencing of CA2 significantly reduced seizure frequency, consistent with a role of CA2 in promoting seizure generation and/or propagation (Whitebirch et al, 2022). In the present study we explored the basis of this inhibitory deficit using immunohistochemical and electrophysiological approaches.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…We recently found that in the pilocarpine-induced status epilepticus mouse model of TLE there was an increase in CA2 intrinsic excitability associated with a loss of CA2 synaptic inhibition. Furthermore, chemogenetic silencing of CA2 significantly reduced seizure frequency, consistent with a role of CA2 in promoting seizure generation and/or propagation (Whitebirch et al, 2022). In the present study we explored the basis of this inhibitory deficit using immunohistochemical and electrophysiological approaches.…”
mentioning
confidence: 58%
“…Our goal here was to provide a detailed quantitative investigation into how the various hippocampal cornu ammonis regions (CA1, CA2 and CA3) are affected in the PILO-SE mouse model of TLE, with particular attention to the mechanisms underlying our previously characterized loss of synaptic inhibitory drive onto CA2 pyramidal cells (Whitebirch et al, 2022). In our previous and current study, we characterized the alterations in the electrophysiological properties of CA2 neurons in acute hippocampal slices from PILO-SE mice that were F1 hybrids from a cross between C57BL/6J and 129S1/SvlmJ mouse lines.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations